Mapping SMA/MA In Surakarta City Using Multidimensional Scaling - Aviory, Koryna; Nuryani, Christina Eva (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
The Competency-Based National Examination (CBNE) was held in 2019. The quality of schools can be determined based on the results of it. The purpose of the study was to map high schools / MA in Surakarta City based on its scores in 2018/2019. The number of SMA/MA is 33, both public and private. Data analysis using multidimensional scaling based on the characteristics of CBNE scores in the Indonesian, English, Mathematics, Physics, Chemistry, and Biology exam subjects. The results showed that there were four groups. They were mapped based on the level of similarity of CBNE scores with the characteristics in each exam. SMA/MA mapping is expected to help the community in choosing schools based on the competencies to be developed by students. School clustering means that there is educational inequality in the context of learning outcomes. This is influenced by a wide variety of factors. This research is expected to be the first step for further research in improving student learning outcomes.